Ant Colony Optimization Ant Colony Optimization untuk menyelesaikan perutean distribusi Snack dengan Vehicle Routing Problem - Endang Setyati; Ine Juniwati (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2022)
One of the main challenges faced by the community in their daily activities is the problem of transportation. Transportation of goods and services is an important topic that attracts the attention of the business world today. Closely related to the transportation sector is the Vehicle Routing Problem (VRP). The VRP variant used in this study is the Capacitated Vehicle Routing Problem (CVRP) which uses the capacity limit of the vehicle used. CVRP is used to minimize the distribution route of goods at IKM Snack FITRIA located in Sidoarjo. The problem of distribution at IKM Snack FITRIA is how to manage the route of shipping goods from the warehouse to a number of shops/customers scattered in various places in Surabaya, Sidoarjo and Gresik efficiently. This research includes planning the route of each transport vehicle in delivering products to consumers spread over several points originating from one depot. The vehicle in one day sends goods from the warehouse to the customer with one delivery. While the algorithm used is Ant Colony Optimization (ACO). ACO is used because it is able to show the best route for the optimal solution of 98%. And get a minimum total mileage with a low level of variance.